2018
DOI: 10.1038/s41598-018-22920-7
|View full text |Cite
|
Sign up to set email alerts
|

Helminth infection protects against high fat diet-induced obesity via induction of alternatively activated macrophages

Abstract: Epidemiological studies indicate an inverse correlation between the prevalence of the so-called western diseases, such as obesity and metabolic syndrome, and the exposure to helminths. Obesity, a key risk factor for many chronic health problems, is rising globally and is accompanied by low-grade inflammation in adipose tissues. The precise mechanism by which helminths modulate metabolic syndrome and obesity is not fully understood. We infected high fat diet (HFD)-induced obese mice with the intestinal nematode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 59 publications
11
57
0
Order By: Relevance
“…Experiments from our laboratory and others have shown that helminth infections attenuate obesity induced by HFD in mouse models, 15,[20][21][22] supporting the inverse correlation between helminth infections and obesity observed in clinical studies. In the current work, we investigated whether the protective effect of helminth infection against HFD obesity is dependent on the H polygyrus-induced Th2 immune response.…”
Section: H Polygyrus Infection Protects Wild-type But Not Stat6 -/-Misupporting
confidence: 76%
See 1 more Smart Citation
“…Experiments from our laboratory and others have shown that helminth infections attenuate obesity induced by HFD in mouse models, 15,[20][21][22] supporting the inverse correlation between helminth infections and obesity observed in clinical studies. In the current work, we investigated whether the protective effect of helminth infection against HFD obesity is dependent on the H polygyrus-induced Th2 immune response.…”
Section: H Polygyrus Infection Protects Wild-type But Not Stat6 -/-Misupporting
confidence: 76%
“…[12][13][14] We have shown recently that infection of mice with the intestinal helminth parasite H polygyrus significantly attenuated high-fat diet (HFD)induced obesity and that this attenuation was associated with enhanced Th2/Treg responses and M2 macrophage polarization. 15 The intestinal microbiota is a complex and dynamic ecosystem, which is composed of trillions of microbes that reside in the gut and plays a significant role in health and disease. 16 It has been found that the composition of the intestinal microbiota differs between obese and healthy people and that altering the microbiota can alleviate obesity.…”
mentioning
confidence: 99%
“…In contrast, the prevalence of inflammatory metabolic diseases, such as Type 2 diabetes mellitus (T2DM) is high in high-income countries. The absence of exposure to helminth infections has been postulated as one mechanism to explain this markedly increased prevalence of T2DM [2][3][4][5][6]. Recent observational studies in India, Indonesia, China and Australia have reported that the prevalence of helminth infections was significantly lower in T2DM individuals compared to non-diabetic controls [4,5,7,8], thus confirming a protective effect of helminths against T2DM pathogenesis.…”
Section: Introductionmentioning
confidence: 98%
“…The first study by Su and colleagues showed that H. polygyrus infection provided protection against DIO by increasing thermogenesis via M2 macrophage recruitment (Figure 2). 69 The second study by Shimokawa et. al.…”
Section: Impact Of Helminth Infection On Type 2 Immune Cell Function mentioning
confidence: 99%
“…Finally, two other studies used H. polygyrus, a natural murine helminth, to investigate the ability of infection to induce adaptive thermogenesis . The first study by Su and colleagues showed that H. polygyrus infection provided protection against DIO by increasing thermogenesis via M2 macrophage recruitment (Figure ) . The second study by Shimokawa et.…”
Section: Helminth Infection and Metabolic Statusmentioning
confidence: 99%